Internet of things, smart spaces, and next generation networks and systems : 18th International Conference, NEW2AN 2018, and 11th Conference, ruSMART 2018, St. Petersburg, Russia, August 27-29, 2018, Proceedings /: 18th International Conference, NEW2AN 2018, and 11th Conference, ruSMART 2018, St. Petersburg, Russia, August 27-29, 2018, Proceedings. (2018) - Unknown
No abstract available